Galaxy evolution in the VIMOS public extragalactic redshift survey (VIPERS) - Davidzon, Iary <1984> (Alma Mater Studiorum - Università di Bologna, 2014)
In this work I present the first measurements of the galaxy stellar mass function (GSMF) from the first public release of the VIPERS catalogue, containing ∼55,000 objects. First, I present the survey design, its scientific goal, the redshift measurements and validation. Then, I provide details about the estimate of galaxy stellar masses, star formation rates, and other physical quantities. I derive the GSMF of different galaxy types (e.g. active and passive galaxies) and as a function of the environment (defined through the local galaxy density contrast). These estimates represent new observational evidence useful to characterise the mechanism of galaxy evolution.